Ultrasonographic monitoring of early pregnancy development in Murrah buffalo heifers (Bubalus bubalis) - Ferreira, João Carlos Pinheiro [UNESP]; Martin, Ian [UNESP]; Irikura, Cristiane Rumi [UNESP]; Gimenes, Lyndsay Unno [UNESP]; Fujihara, Caroline Junko [UNESP]; Jorge, Andre Mendes [UNESP]; Oba, Eunice [UNESP] (Elsevier B.V., 2011)
The aim of the current study was to monitor the early pregnancy development in buffalo heifers and establish biometric threshold of different gestational vesicle and embryo/fetal parts from the day 15 following fertilization to day 70. Serial daily ultrasonographic examinations were carried out on eleven pregnant buffalo-heifers, during which the gestational vesicle diameter, amniotic vesicle diameter, crown-rump length, trunk diameter and biparietal diameter were measured and embryo/fetal sex characteristics were determined. The gestational vesicle, embryo and its heartbeats were assessed, respectively, by gestational days (d) 20.55 +/- 2.34; 25.18 +/- 1.91 and 25.27 +/- 3.58 of pregnancy. The liquid column in nonpregnant horn and amniotic vesicle were detected, respectively, by d 31.0 +/- 3.83 and 31.64 +/- 2.34 of pregnancy. Subsequently were sequentially detected the neural tube (d 33.0 +/- 3.51), umbilical cord (d 0.25 +/- 2.76), early limbs, (d 41.67 +/- 4.85), embryos proper movement (d 46.25 +/- 236), vertebral column (d 4733 +/- 4.9), genital tubercle (d 47.2 +/- 3), fetal bones (d 56.56 +/- 1.67), brain (d 57.5 +/- 1.2), urinary bladder (d 57.88 +/- 3.08), stomach cavities (d 59.17 +/- 436), brain ventricles (d 61.09 +/- 234), end of migration of genital tubercle in males (d 58.4 +/- 2.2) and in females (d 60.4 +/- 4.2), skull acoustic shadow (d 59.66 +/- 3.13), vertebra acoustic shadow (d 62.14 +/- 3.13), ribs acoustic shadow (d 64 +/- 2.65), limb bones acoustic shadow (d 65 +/- 1.58) and liver (d 66.63 +/- 3.54). High regression and correlation coefficients were found between different studied parameters and gestational age, where the highest were found for the crown-rump length and biparietal diameter. In conclusion, the overall data indicated the feasibility and value of ultrasonographic embryo, fetal and vesicle characteristics and embryo/fetometry in buffaloes for the evaluation of fetal development and estimation of gestational age during the first 70th pregnancy days. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Buffalo heifers; Early pregnancy; Ultrasonographic monitoring